Polyphosphate fertilizer impacts the enzymatic and non-enzymatic antioxidant capacity of wheat plants grown under salinity - Loudari, Aicha; Latique, Salma; Mayane, Asmae; Colinet, Gilles; Oukarroum, Abdallah (Scientific reports, 2023)
By 2050, the predicted global population is set to reach 9.6 billion highlighting the urgent need to increase crop productivity to meet the growing demand for food. This is becoming increasingly challenging when soils are saline and/or deficient in phosphorus (P). The synergic effect of P deficiency and salinity causes a series of secondary stresses including oxidative stress. Reactive Oxygen Species (ROS) production and oxidative damage in plants caused either by P limitation or by salt stress may restrict the overall plant performances leading to a decline in crop yield. However, the P application in adequate forms and doses could positively impact the growth of plants and enhances their tolerance to salinity. In our investigation, we evaluated the effect of different P fertilizers forms (Ortho-A, Ortho-B and Poly-B) and increasing P rates (0, 30 and 45 ppm) on the plant's antioxidant system and P uptake of durum wheat (Karim cultivar) grown under salinity (EC = 3.003 dS/m). Our results demonstrated that salinity caused a series of variations in the antioxidant capacity of wheat plants, at both, enzymatic and non-enzymatic levels. Remarkably, a strong correlation was observed between P uptake, biomass, various antioxidant system parameters and P rates and sources. Soluble P fertilizers considerably enhanced the total plant performances under salt stress compared with control plants grown under salinity and P deficiency (C+). Indeed, salt-stressed and fertilized plants exhibited a robust antioxidant system revealed by the increase in enzymatic activities of Catalase (CAT) and Ascorbate peroxidase (APX) and a significant accumulation of Proline, total polyphenols content (TPC) and soluble sugars (SS) as well as increased biomass, Chlorophyll content (CCI), leaf protein content and P uptake compared to unfertilized plants. Compared to OrthoP fertilizers at 45 ppm P, Poly-B fertilizer showed significant positive responses at 30 ppm P where the increase reached + 18.2% in protein content, + 156.8% in shoot biomass, + 93% in CCI, + 84% in shoot P content, + 51% in CAT activity, + 79% in APX activity, + 93% in TPC and + 40% in SS compared to C+. This implies that PolyP fertilizers might be an alternative for the suitable management of phosphorus fertilization under salinity.